2022
DOI: 10.1002/aur.2860
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual temporal binding window narrows with age in autistic individuals

Abstract: Atypical sensory perception has been recognized in autistic individuals since its earliest descriptions and is now considered a key characteristic of autism. Although the integration of sensory information (multisensory integration; MSI) has been demonstrated to be altered in autism, less is known about how this perceptual process differs with age. This study aimed to assess the integration of audiovisual information across autistic children and adolescents. MSI was measured using a non‐social, simultaneity ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Further, we provided evidence that audiovisual speech perception in noise follows a developmental trajectory (Ross et al, 2011) where MS (multisensory) deficits can be observed up to the age of 12 years after which they appear to ameliorate (Beker et al, 2018; Foxe et al, 2015). Recent support for this developmental amelioration of MS processing deficits comes from a study by Ainsworth et al (Ainsworth & Bertone, 2022). The investigators observed that the temporal binding window for MS stimuli narrowed with age from childhood (6–12 years) to adolescence (13–18 tears) in an ASD sample indicating increasing sensitivity to temporal alignment of stimuli.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, we provided evidence that audiovisual speech perception in noise follows a developmental trajectory (Ross et al, 2011) where MS (multisensory) deficits can be observed up to the age of 12 years after which they appear to ameliorate (Beker et al, 2018; Foxe et al, 2015). Recent support for this developmental amelioration of MS processing deficits comes from a study by Ainsworth et al (Ainsworth & Bertone, 2022). The investigators observed that the temporal binding window for MS stimuli narrowed with age from childhood (6–12 years) to adolescence (13–18 tears) in an ASD sample indicating increasing sensitivity to temporal alignment of stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…T A B L E 1 1 Significant differences between typically developed (TD) and autism spectrum disorder (ASD) groups in the asynchronous audiovisual condition (AVa) condition. developmental amelioration of MS processing deficits comes from a study by Ainsworth et al (Ainsworth & Bertone, 2022). The investigators observed that the temporal binding window for MS stimuli narrowed with age from childhood (6-12 years) to adolescence (13-18 tears) in an ASD sample indicating increasing sensitivity to temporal alignment of stimuli.…”
Section: Asd > Tdmentioning
confidence: 99%
“…An important further consideration is that the majority of the existing research examining differences in audiovisual temporal processing among autistic individuals has been conducted with children and adolescents (e.g., de Boer‐Schellekens et al, 2013; Stevenson, Siemann, et al, 2014). Recent evidence suggests that multisensory processing differences in autistic individuals may diminish during adolescence and later development (Ainsworth & Bertone, 2023; Foxe et al, 2015), and so while investigating changes associated with development is not an aim of this research project, investigating audiovisual temporal processing in a group of autistic adults may provide some evidence toward indicating if reduced sensitivity to audiovisual asynchrony associated with ASD persists later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Narrowing of this window, which can be seen as a refinement of temporal processing acuity, occurs during typical development (Hillock et al, 2011; Hillock‐Dunn & Wallace, 2012; Lewkowicz & Flom, 2014) but is both delayed and diminished among those with autism (de Boer‐Schellekens et al, 2013; Foss‐Feig et al, 2010; Stevenson, Siemann, et al, 2014). However, recent research challenges the degree to which this applies to autistic adults (Ainsworth & Bertone, 2023; Weiland et al, 2022; Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%